An innovation of Event Management and Attendance System for Students' Activities (eMats) / Muhammad Farid Ahmat … [et al.] - Ahmat, Muhammad Farid; A, M. Nazri; H.J, M. Luqman; B.R., M Abid; Noradzan, Haslinda (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
Recording attendance for students' activities organized by faculty has become a potential process to be automated using the web-based system. Manual process of recording attendance before this was not systematic and faced difficulties in storing, retrieving, and generating report from the records. This manual system is not reliable since it has tendency in losing the attendance data such as missing attendance sheets or problems in generating report for future use. By developing a web-based system for event management and attendance, recording attendance and generating report become easier and eliminates the problems through the process. To complete system functionality, the attendance system uses barcode scanner as a device to record the attendance automatically. The system is capable for recording attendance, submitting attendance list via email, viewing the event organized by the faculty, and generating attendance reports. The system has great potential to be commercialized since it is comprehensive, effective and efficient, thus can give benefits in helping automating the event attendance and management for societies and organizations.